Teacher’s Strategy in Solving EFL Students’ Problems in Learning English - Ariyanti Ariyanti; Widi Syahtia Pane; Umar Fauzan (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2019)
Learning new language is never been so easy to master where there must be challenges that teachers face in classroom. The aim of this research is to investigate an English teacher in teaching English as a foreign language to junior high school students at Ma’had Tahfidzul Qur’an, Samarinda, East Kalimantan, Indonesia. The matters to be investigated include barriers the teacher faced as well as her strategies to solve the problems. The result of semi-structured interview showed that the biggest challenge faced by the English teacher is the condition where the students are less-motivated in learning English. Several strategies are used by the teacher such as encourage the students through verbal motivation as well as provide joyful activities such as conducted different kind of games to build positive mood and interest of students in leaning a new language. The use of proper teaching strategies is demanded in order to have English learning become students’ habit. Therefore, implication of language teaching methodologies is also discussed in this research.